Strategies For An Effective Distributed Pair Programming - Mario Elyezer Subekti Simaremare (Jurnal Mantik, 2022)
Pair programming is an old yet effective method in solving programming problems in the computer science field. Here, at Institut Teknologi Del, we employed this method in the early programming courses to help the students master the learning objectives and practice them by solving problems in a collaborative manner. The COVID-19 pandemic was started in early 2020, it threatened almost every sector in our lives including education. Students were sent home and the learning process was forced to switch from in-person to distancing learning. This situation was a true challenge for our traditional pair programming approach where the students used to work together side-by-side. We then adapt the approach to fit the distributed setting. In this paper, we would like to share our experience in applying distributed pair programming, the problems we faced, and the strategies we employed to achieve the highest learning impacts.